Effects of Different Signalling Pathways on Regulation of 'GLK' GARP Transcription Factors in 'Arabidopsis thaliana' - Ponomareva, Ekaterina (Université d'Ottawa / University of Ottawa, 2012)
GLK1 and GLK2 transcription factors have been suggested to be involved in the regulation of chloroplast development, organic nitrogen signaling, disease resistance and circadian rhythmicity (Waters et al. 2009; Gutiérrez et al. 2008; Savitch et al. 2007; Sprott et al. 2010). This implies that multiple factors may play roles in regulation of GLK genes. In the present study, transcriptional regulation of GLK1 and GLK2 in Arabidopsis by various endogenous and environmental stimuli was investigated with the objective of elucidating the primary signalling pathway affecting expression of these two genes. Collectively, results of GLK1 and GLK2 expression in response to the experimental treatments of Arabidopsis point to the regulation of the two genes by changes in photosynthetic metabolism and reactive oxygen species (ROS) levels, and by organic nitrogen signalling. Changes in ROS levels and organic nitrogen signalling may also affect the two genes indirectly by interfering with or altering photosynthetic metabolism.
Keywords: Golden2-like; GLK1; GLK2; transcription factors; photosynthesis; gene expression